Organic Geochemistry and Source Rock Potential of Naokelekan Formation in Selected Wells, North Iraq - Ismael, Jan I. (Asian Review of Environmental and Earth Sciences, 2018)
In this study, organic geochemical characteristics and potential of Upper Oxfordian–Lower Kimmeridgian aged bituminous shale beds in Naokelekan formation (North Iraq) were investigated by using TOC and pyrolysis analyses. The Total Organic Carbon (TOC) contents for the studied samples varying between from 0.46-21.33%, average 7.06% and Taq Taq-1 well as good hydrocarbon potential (0.85-1.66 %, with average of 1.06%), whereas Jk-1 well can be rated as an very good hydrocarbon potential from 1.04-4.16 %, with average of 2.15 %. The low Hydrogen Index (HI = 24-605 mg HC/g TOC) for Bj-1 well, (HI = 147-673 mg HC/g TOC) in the Jk-1 well while in Taq Taq-1 well (HI = 9-48 mg HC/g TOC) indicate that kerogen type for the vast majority of the studied samples is Type II/I for Bj-1 well and Type IV with few samples, Type of I and II kerogens in the Taq Taq-1 and Jk-1 well. Consequently most of the organic matter of Bj-1 and Jk-1 well tends to generate petrol, even though a small portion of them exhibit a tendency to generate gas. While all samples of Taq Taq-1 well tends to generate gas. The studied bituminous rock samples characterized by low Tmax (434-602 °C) for Bj-1,Taq Taq-1 (344-429 °C) and (419-602 °C) for Jk-1 well. These values show, in terms of potential of hydrocarbon generation, that the studied samples have a source rock potential of organic matter from immature to over mature. Additionally, the S1 hydrocarbon type values indicate no external contribution of migrated hydrocarbons to the bituminous rocks of the studied area.